Segmental aqueous humour outflow and eye orientation have strong influence on ocular drug delivery - Loke, Chai Yee; Ooi, Ean Hin; Salahudeen, Mohmed S.; Ramli, Norlina Mohd; Samsudin, Amir (Elsevier, 2018)
The present study is motivated by the recent concerns raised over the existence of segmental outflow and its implications on ocular drug delivery. A 3D model of the human eye is developed, where hydrodynamic and mass transport analyses after eye drop instillation, are carried out. To model segmental outflow, the permeability of the trabecular meshwork (TM) is assumed to vary spatially following a rectangular function. The choice of the rectangular function is based on the results from the tracer distribution study of Chang et al., 2014. Results from the numerical simulations show that segmental outflow causes the majority of the available drugs to egress through the active region, while non-active region experiences very minimal drug exposure. This supports the experimental findings of Chang et al. Additionally, it was found that eye orientation can affect the delivery of ophthalmic drugs by influencing the aqueous humour hydrodynamics. The results obtained here suggest that there may be a need to re-evaluate the design of ocular drug delivery system by taking into consideration the effects of segmental outflow and eye orientation.